Belastungs-Beanspruchungsprofil im Fußball aus physiologischer Sicht - Tschan, H.; Baron, R.; Smekal, G.; Bachl, N. (Österreichisches Journal für Sportmedizin, 2001)
This article is intended to highlight the physiological demands that are relevant to success in the game of soccer. Three broad areas are covered: 1. Time motion characteristics representing the physiological load imposed on top-level soccer players. 2. Physiological profile of soccer. Pattern of physiological response to participation in soccer evaluated from different measurements during and after the game. 3. Performance diagnostics in soccer.